Lead corrosion and formation of lead oxides from a lead-air cell in methanesulfonic acid - Basirun, Wan Jefrey; Saeed, I.M.; Ghadimi, H.; Ladan, M.; Mahmoudian, M.R.; Ebadi, M.; Abdulrauf, L.B.; Endut, Z. (Ecole Polytechnique de Montreal, 2016)
The corrosion of lead in methanesulfonic acid solution in the presence of a MnO2 air cathode in a primary lead-air cell is investigated. The highest power density of the lead-air cell is 2.8 mW cm-2. X-ray photoelectron spectroscopy and powder X-ray diffraction results demonstrate the formation of lead (II) oxide and lead (IV) dioxide on the air cathode after continuous discharge. Field emission scanning electron microscopy image shows that the surface coverage of lead (II) oxide and lead (IV) dioxide on the air cathode is only partial and will allow oxygen reduction.